MEASUREMENT OF ANXIETY LEVEL USING THE DEPRESSION ANXIETY SCALE (DASS) ANXIETY MEASUREMENT ON PREGNANT WOMEN IN DEALING WITH DELIVERY IN REMOTE WATER AREA AND FACTORS THAT INFLUENCE IT IN DABONG VILLAGE, BA DISTRICT, KUBUTAN, 2022. - Fiteriya Fiteriya; Nanik Yuliwati (Lembaga Pengembangan Kinerja Dosen, 2022)
Excessive anxiety can affect pregnancy and fetal growth. Irrational anxiety makes pregnant women uneasy and triggers stress. Babies born to stressed mothers tend to be hyperactive children and have difficulty controlling emotions(Maulana, 2016). To determine the level of anxiety of pregnant women and the factors that influence it in dealing with childbirth anxiety in the remote waters of Dabong Village, Kubu District, Kubu Raya Regency, West Kalimantan. The research methodology uses this research method using an analytical research method with a Cross Sectional approach. The sample in this study were 31 pregnant women respondents. Data analysis using univariate and bivariate data analysis. The sampling technique used was total sampling. The research instrument consisted of a DASS (Depression Anxiety Stress Scale) questionnaire for anxiety levels. Data were analyzed using Chi-square statistical test to determine the relationship between two independent variables and the dependent variable, namely the level of anxiety and the factors that influence it (age, education, occupation, parity, level of knowledge). The results of the univariate data analysis showed that the anxiety level of many pregnant women experienced anxiety with a mild level of 12 pregnant women, 7 pregnant women, 6 pregnant women heavy. Bivariate data analysis with statistical test results obtained p value = 0.018 for age, statistical test results obtained p value = 0.043 for education, statistical test results obtained value for work p = 0.035, statistical test results obtained p value = 0.024 for parity and test results statistically obtained p value = 0.029 for the level of knowledge, on the anxiety of pregnant women, it can be concluded that there is an effect of the level of anxiety of pregnant women on anxiety in facing childbirth and the factors that influence it, The conclusion of the study is that pregnant women experience anxiety with levels of anxiety from mild to severe and there is an influence on the level of anxiety of pregnant women on anxiety in facing childbirth. There is a need for health education related to pregnancy and focusing on the psychology of pregnant women as well as family support, husbands (active roles) and the environment for pregnant women. Anxiety assessments for pregnant women are also carried out.